PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING MENGGUNAKAN LIVEWORKSHEETS PADA ELEMEN PENGUKURAN PEMBELAJARAN MATEMATIKA DI KELAS IV SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to produce a valid, practical, and effective e-LKPD product based on problem-based learning using live worksheets on the measurement elements of mathematics learning in grade IV of elementary school. The background of this research is the minimal use of technology in the learning process in elementary schools. This research is a type of development research using a Research and Development (R&D) approach. This study uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study were fourth-grade students at SDN 06 Lumindai, SDN 15 Lumindai, and SDN 29 Lumindai. The types of data used in this study are qualitative and quantitative data. The instruments used were interviews, observations, questionnaires, and tests. The results of the study obtained a validity level with a percentage of 94.23% with the category